2015
DOI: 10.1021/acs.orglett.5b00955
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies toward the C32–C46 Segment of Hemicalide. Assignment of the Relative Configuration of the C36–C42 Subunit

Abstract: The synthesis of five diastereomeric model compounds incorporating the C32-C46 segment of the antitumor marine natural product hemicalide has been achieved through a convergent approach relying on the 1,4-addition of an alkenyl boronate to an α,β-unsaturated δ-lactone followed by α-hydroxylation of an enolate and a Julia-Kocienski olefination. Comparison of the (1)H and (13)C NMR data of the model compounds with those of hemicalide enabled the assignment of the relative configuration of the C36-C42 subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Initially, the NMR shifts of all possible 16 isomers of the virtual fragment 45 were calculated, and the fragment 45A was identified as the preferred candidate in 84% probability ( Figure 11). Since this assignment challenged the findings of Cossy and co-workers 34 (compound 37, Figure 9), the computational predictions were revised. In particular, the NOE correlation experimentally observed between H-37 and H-40 clearly confirmed that both protons should be on the same side of the molecule, which was not the case in 45A.…”
Section: Hemicalidementioning
confidence: 90%
See 4 more Smart Citations
“…Initially, the NMR shifts of all possible 16 isomers of the virtual fragment 45 were calculated, and the fragment 45A was identified as the preferred candidate in 84% probability ( Figure 11). Since this assignment challenged the findings of Cossy and co-workers 34 (compound 37, Figure 9), the computational predictions were revised. In particular, the NOE correlation experimentally observed between H-37 and H-40 clearly confirmed that both protons should be on the same side of the molecule, which was not the case in 45A.…”
Section: Hemicalidementioning
confidence: 90%
“…In good agreement with their previous work, a nice match between the 1 H and 13 C NMR shifts corresponding to the C-8/C-24 region of the synthesized compound with those of hemicalide was observed (Dd up to 0.12 and 1.2 ppm, respectively). 33 In the meantime, Cossy and co-workers 34 decided to study the C-36/C-46 unit. In view of the six stereocenters in that region, up to 32 possible diastereoisomers might be postulated.…”
Section: Hemicalidementioning
confidence: 99%
See 3 more Smart Citations